MDR1-Mediated Drug Resistance in Candida dubliniensis - Wirsching, Stephanie (American Society for Microbiology, 2001)
Candida dubliniensis is a recently described opportunistic fungal pathogen that is closely related to Candida albicans. Candida dubliniensis readily develops resistance to the azole antifungal agent fluconazole, both in vitro and in infected patients, and this resistance is usually associated with upregulation of the CdMDR1 gene, encoding a multidrug efflux pump of the major facilitator superfamily. To determine the role of CdMDR1 in drug resistance in C. dubliniensis, we constructed an mdr1 null mutant from the fluconazole-resistant clinical isolate CM2, which overexpressed the CdMDR1 gene. Sequential deletion of both CdMDR1 alleles was performed by the MPA(R)-flipping method, which is based on the repeated use of a dominant mycophenolic acid resistance marker for selection of integrative transformants and its subsequent deletion from the genome by FLP-mediated, site-specific recombination. In comparison with its parental strain, the mdr1 mutant showed decreased resistance to fluconazole but not to the related drug ketoconazole. In addition, we found that CdMDR1 confers resistance to the structurally unrelated drugs 4-nitroquinoline-N-oxide, cerulenin, and brefeldin A, since the enhanced resistance to these compounds of the parent strain CM2 compared with the matched susceptible isolate CM1 was abolished in the mdr1 mutant. In contrast, CdMDR1 inactivation did not cause increased susceptibility to amorolfine, terbinafine, fluphenazine, and benomyl, although overexpression of CdMDR1 in a hypersusceptible Saccharomyces cerevisiae strain had previously been shown to confer resistance to these compounds. The effect of CdMDR1 inactivation was identical to that seen in two similarly constructed C. albicans mdr1 mutants. Therefore, despite species-specific differences in the amino acid sequences of the Mdr1 proteins, overexpression of CaMDR1 and CdMDR1 in clinical C. albicans and C. dubliniensis strains seems to confer the same drug resistance profile in both species.